Kebijakan Pendidikan Berbasis Keunggulan Lokal di Provinsi Maluku: Analisis Kritis dalam Perspektif Teori Kebijakan Modern dan Siklus Kebijakan - Arsyil Waritsman; Tanwey Gerson Ratumanan; Theresia Laurens (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to analyze the local excellence-based education policy in Maluku Provincial Regulation Number 7 of 2019 concerning the Implementation of Education. The background of the study is based on the importance of education that is not only oriented towards national standards, but also able to accommodate the social, cultural, and geographical characteristics of the island regions in Maluku Province. The local excellence-based education policy is seen as strategic for strengthening cultural identity, increasing the relevance of education, and supporting the development of regional human resources. This study uses a qualitative method with a public policy analysis approach. Data collection techniques were carried out through a documentation study of Maluku Provincial Regulation Number 7 of 2019 and various relevant education indicators. The analysis was conducted using modern policy theory, policy cycles, and critical analysis of education policy. The results of the study indicate that the local excellence-based education policy in Maluku has a progressive orientation because it integrates local culture, character education, local content curriculum, and the development of regional potential into the education system. However, the implementation of the policy still faces various challenges, such as unequal access to education in the island region, limited infrastructure, low teacher competency in local content development, weak integration of education with local economic needs, and suboptimal education governance and funding.